2021
DOI: 10.1007/s11030-021-10258-8
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of ( ±)-3-(1H-pyrazol-1-yl)-6,7-dihydro-5H-[1,2,4]triazolo[3,4-b][1,3,4] thiadiazine derivatives with promising in vitro anticoronavirus and antitumoral activity

Abstract: A new series of ( ±)- (3-(3,5-dimethyl-1H-pyrazol-1-yl)-6-phenyl-6,7-dihydro-5H-[1,2,4]triazolo [3,4-b][1,3,4]thiadiazin-7-yl)(phenyl)methanones were efficiently synthesized starting from 4-amino-5-hydrazinyl-4H-1,2,4-triazole-3-thiol 1, acetyl acetone 2, various aromatic and heterocyclic aldehydes 3 and phenacyl bromides 4. All the newly synthesized compounds were tested for their antiviral and antitumoral activity. It was shown that subtle structural variations on the phenyl moiety allowed to tune biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Recently, pyrazole and dihydrothiadiazine skeletons were obtained by a one-pot four-component reaction [ 110 ]. Initially, a mixture of acetylacetone 118 , 4-amino-5-hydrazinyl-4 H -1,2,4-triazole-3-thiol 119 , and diverse aldehydes 1 catalyzed by one drop of concentrated HCl in refluxing ethanol for 5–7 h afforded pyrazole-based intermediates 120 ( Scheme 13 ).…”
Section: Multicomponent Synthesis Of Biologically Active Pyrazole Der...mentioning
confidence: 99%
“…Recently, pyrazole and dihydrothiadiazine skeletons were obtained by a one-pot four-component reaction [ 110 ]. Initially, a mixture of acetylacetone 118 , 4-amino-5-hydrazinyl-4 H -1,2,4-triazole-3-thiol 119 , and diverse aldehydes 1 catalyzed by one drop of concentrated HCl in refluxing ethanol for 5–7 h afforded pyrazole-based intermediates 120 ( Scheme 13 ).…”
Section: Multicomponent Synthesis Of Biologically Active Pyrazole Der...mentioning
confidence: 99%
“…It has been considered a supernatural moiety or magic moiety [37][38][39][40][41]. Thiadiazine-based substances exhibit antiproliferative activity against a number of in vitro cancer cell lines, including lung carcinoma (A549), hepatocellular carcinoma (Hep3B), breast cancer (MCF-7), and prostate (PC-3), by targeting and interfering with DNA and stimulating cell cycle arrest, which causes cancer cells to undergo apoptosis [42][43][44]. Another class of heterocyclic compounds containing pyridine and thiazole moieties was designed, synthesized, and characterized by various spectral approaches.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that small changes in the structure of the phenyl group could change the biological qualities to make them more effective against viruses or tumors. These compounds have the ability to fight tumors due to stopping tubulin from polymerizing [ 63 ].…”
Section: Synthesis Of Triazolo[34- B ]Thiadiazinesmentioning
confidence: 99%